FAKTOR-FAKTOR YANG MEMPENGARUHI AUDITOR SWITCHING (STUDI EMPIRIS PADA PERUSAHAAN REAL ESTATE DAN PROPERTY YANG TERDAFTAR DI BURSA EFEK INDONESIA 2007-2012) - Yulya Pinkasari; Kirmizi Ritonga; Al Azhar Ali (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The main purpose of this research is examining and knowing the efffects of management stock ownership, dividend policy, financial distress, the number of commissioners, management changes, audit tenure, going concern opinion, public accountant firm’s size, and change percentage of return on assets (ROA) to auditor switching. The population in this study were real estate and property firm listing in Indonesia Stock Exchange period 2007-2012, with the population total 48 firms. the sample are taken using purposive sampling method, and there are 84 of financial reports that have the sampling criteria. Type and data source in this study is decumentary and secondary data such as annual financial statement and independence auditor report. The data analysis technique used to verify the hypothesis is logistic regression. The result of this research show that audit tenure has significant effect on auditor switching. Then, management stock ownership, dividend policy, financial distress, the number of commissioners, management changes, going concern opinion, public accountant firm’s size, and change percentage of return on assets (ROA) does not have significant effect on auditor switching.Keywords: auditor switching, dividend policy, financial distress, management changes, and going concern opinion.